Implications Of Digital Transformation and Cultural Conflict at PT. Bank Amanah Rakyat - Ivon Harnela Wahana; Depit Hariyanto; Herina; Syaiful Bahri; Akhmad Mauliady (PT. Hanken Sukses Jaya, 2025)
This research aims to analyze digital transformation and organizational culture at PT. Bank Amanah Rakyat (BAR), as a medium-sized bank with a conservative organizational culture, faces serious challenges in the implementation of the